Metal organic framework nanofibers derived Co3O4-doped carbon-nitrogen nanosheet arrays for high efficiency electrocatalytic oxygen evolution. (October 2018) - Kuang, Xuan; Luo, Yucheng; Kuang, Rui; Wang, Zhiling; Sun, Xu; Zhang, Yong; Wei, Qin
Abstract: Despite significant advances in preparing functional carbon and transition metal oxide (TMO) nanomaterials arising from metal–organic frameworks (MOFs), the TMO nanoparticles (NPs) incorporated on 2D carbon-nitrogen nanosheet arrays constructed from MOF structure have not been explored before. Herein, a facile self-assembly methodology for MOF nanofibers derived Co3 O4 NPs doped carbon-nitrogen nanosheet arrays anchored on Ni foam (Co3 O4 @C-N NSA/NiF) is reported. Co(II)-MOF nanofiber arrays are electrodeposited directly on Ni foam at room-temperature. Then after pyrolysis at 300 °C for 2 h in air, the periodic arrangement of metal Co(II) ion nodes and nitrogen-rich organic moieties in the Co(II)-MOF scaffolds are successfully converted into carbon-nitrogen nanosheet arrays imbeded small Co3 O4 NPs. Co3 O4 @C-N NSA/NiF directly as binder-free electrode for oxygen evolution reaction (OER) catalyst, only needs low overpotentials of 245 mV to drive catalytic current densities of 25 mA cm −2 in 1.0 M KOH, which is superior to other MOF-derived catalysts. Co3 O4 @C-N NSA/NiF also demonstrates low resistance, outstanding durability with a high turn-over frequency of 0.958 s −1 at an overpotential of 370 mV. The enhanced OER performance arises from that Co3 O4 NPs uniformly anchored on sp 2 -hybridized carbon-nitrogen nanosheet array brings about more active sites, boosting mass transport and electron transfer. Graphical abstract: Image 1